1997
DOI: 10.1046/j.1365-3040.1997.d01-80.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes of carbon, water and energy over Brazilian cerrado: an analysis using eddy covariance and stable isotopes

Abstract: We present the energy and mass balance of cerrado sensu stricto (a Brazilian form of savanna), in which a mixture of shrubs, trees and grasses forms a vegetation with a leaf area index of 1-0 in the wet season and 0-4 in the dry season. In the wet season the available energy was equally dissipated between sensible heat and evaporation, but in the dry season at high irradiance the sensible heat greatly exceeded evaporation. Ecosystem surface conductance gî n the wet season rose abruptly to 0-3 mol m"^ s"^ and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
160
2
23

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(212 citation statements)
references
References 49 publications
(35 reference statements)
16
160
2
23
Order By: Relevance
“…Several experimental studies have adressed the carbon exchange using automatic monitoring in the Amazon rain forests as part of the LBA Project (LBA 1996;Grace et al 1996, Malhi et al 1998. Pioneer studies in Brazillian savanna were reported by Miranda et al (1997) in a Cerrado Sensu stricto in the central region, and by Vourlitis et al (2001) in a Cerradão vegetation at the ecotone between tropical savanna and rain forest in Central Brasil. Related investigations in South America about water cycle and carbon stocks in tropical savanna were developed in Venezuela (San Jose et al 2001;Szarzynsky and Anhuf et al 1999).…”
Section: Introductionmentioning
confidence: 94%
“…Several experimental studies have adressed the carbon exchange using automatic monitoring in the Amazon rain forests as part of the LBA Project (LBA 1996;Grace et al 1996, Malhi et al 1998. Pioneer studies in Brazillian savanna were reported by Miranda et al (1997) in a Cerrado Sensu stricto in the central region, and by Vourlitis et al (2001) in a Cerradão vegetation at the ecotone between tropical savanna and rain forest in Central Brasil. Related investigations in South America about water cycle and carbon stocks in tropical savanna were developed in Venezuela (San Jose et al 2001;Szarzynsky and Anhuf et al 1999).…”
Section: Introductionmentioning
confidence: 94%
“…Since trees and grass canopies differ in their ability to intercept and absorb photons and transpire (Kelliher et al, 1993;Miranda, 1997), their relative composition can have a profound effect on the surface energy balance of a landscape, which in turn, can have a modifying feedback on the regional climate (Zeng and Neelin, 2000) and its water balance (Joffre and Rambal, 1993;Rodriguez-Iturbe et al, 1999a).…”
Section: Introductionmentioning
confidence: 99%
“…However, the obtained LAI values were not so different from the values described by Asner (1998) for 30 common species of Cerrado, these ranging from 3.1 to 5.9. Even when subtracting the highest stem area index (SAI) value of 0.7 for Cerrado trees (Asner, 1998), obtained values remained higher than those described by Miranda et al (1997). In another study in five Cerrado sites, Hoffmann et al (2005) found that LAI values ranged from 2.48 in the "cerradão" to 0.28 in the "campo sujo".…”
Section: Discussionmentioning
confidence: 84%
“…For a Eucalypt savanna in Australia, stated that LAI values were typically 1.0 in the wet season and 0.65 in the dry. Even for a Cerrado in central Brazil, Miranda et al (1997) obtained LAI values of 1.0 in the wet and 0.4 in the dry seasons, when considering only a mixture of leaves from shrubs, trees and grass. Values recorded in the Serra do Cipó National Park are may be a little high, because indirectly estimated LAI based on gap-fraction analysis included the projected stem and branch area.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation